Translation Shift Of Noun Phrase In The Dark Knight Rises Movie And Its Subtitling - Ratnawati, Ririn; , Dra. Dwi Haryanti, M.Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
This is descriptive qualitative research. It aims to classify translation shift of noun phrase, and to describe the equivalence and non equivalence of translation shift of noun phrase in The Dark Knight Rises movie which is translated into Indonesian. In collecting data, the writer uses documentation by coding and underlying the English sentence containing noun phrase the subtitle of The Dark Knight Rises movie scripts. From the data data analysis, the researcher finds three translation shifts, namely: level shift, structural shift, and noun phrase is omitted. From 152 data the researcher finds 5 shifts which belongs to level shift (1) noun phrase is translated into noun 88 data or 58%, (2) noun phrase is translated into verb is 8 data or 5%, (3) noun phrase is translated into adverb is 2 data or 1%, (4) noun phrase is translated into adjective is 4 data or 3%, (5) noun phrase is translated into noun+nya is 20 data or 13%. There are two translation shifts which belongs to structural shift. There are 18 data, (1) noun phrase is translated into adverb phrase is 3 data or 2% and (2) noun phrase is translated into prepositional phrase is 15 data or 10%. And there are 12 data or 8% which belongs to noun phrase is omitted. The second result is equivalence translation. From 152 data the researcher divided them into equivalent and not equivalent translation. (1) the equivalent translation is 146 data or 96% and (2) not equivalent translation is 6 data or 4%.